Time Well Spent: Manfaat Psikologis dari Volunteering - Rinanda Rizky Amalia Shaleha; Elita Kurniasari (Universitas Kristen Maranatha, 2023)
This study is a theoretical review that discusses volunteering from psychological, physiological, and cultural aspects. Volunteering is any activity that allocates free time, materials, and energy to other people, groups, or organizations. Volunteers give their time, materials, and energy in many ways. Volunteering became popular in various countries, including Indonesia, with the highest level of volunteering worldwide. Cultural factors (collectivistic vs individualistic) influence volunteering, although there are still inconsistent results. Furthermore, religiosity and levels of social trust contribute to volunteering. Physiological processes such as genetic, hormonal, and neurobiological underlie prosocial behavior. The interaction of these things impacts psychological aspects such as the expression of positive emotions and well-being, regardless of various age ranges. The benefits felt by volunteers are that they have better mental health and health conditions than non-volunteers. Considering the many benefits of volunteering activities, it is expected that there will be persuasive steps involving various stakeholders to invite more people to get involved in all forms of volunteer activities, individual and collective.